2013
DOI: 10.1002/dneu.22072
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone alters genomic responses to song and monoaminergic innervation of auditory areas in a seasonally breeding songbird

Abstract: Behavioral responses to social stimuli often vary according to endocrine state. Our previous work has suggested that such changes in behavior may be due in part to hormone-dependent sensory processing. In the auditory forebrain of female white-throated sparrows, expression of the immediate early gene ZENK (egr-1) is higher in response to conspecific song than to a control sound only when plasma estradiol reaches breeding-typical levels. Estradiol also increases the number of detectable noradrenergic neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 99 publications
2
17
0
Order By: Relevance
“…In contrast, expression of OTR mRNA increased in RA in birds of the TS morph but not the WS morph. Morph-dependent effects of T on the brain are consistent with the findings of Matragrano et al (2013), who reported that T administration reduced serotonergic innervation of the auditory forebrain in WS but not TS males.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, expression of OTR mRNA increased in RA in birds of the TS morph but not the WS morph. Morph-dependent effects of T on the brain are consistent with the findings of Matragrano et al (2013), who reported that T administration reduced serotonergic innervation of the auditory forebrain in WS but not TS males.…”
Section: Discussionsupporting
confidence: 89%
“…We are currently mapping and characterizing the effects of morph on the expression of both genes in the brain, which may ultimately shed light on the mechanisms underlying morph-dependent effects of T-treatment on VTR expression. Our current results, together with the findings of Matragrano et al (2013) on serotonin fiber density, demonstrate a clear mechanism by which hormones may interact with genotype to affect social behavior.…”
Section: Discussionsupporting
confidence: 71%
“…Thresholding was based on the contrast in pixel intensity between specific staining and background and was consistent across brain regions. Threshold levels were checked by eye to ensure that fiber staining corresponded to the pixels selected by ImageJ (Lorentz et al 2010; Matragrano et al 2013). For each image, the area occupied by pixels with an intensity value above the background level was converted to mm 2 and averaged across the group.…”
Section: Methodsmentioning
confidence: 99%
“…However, relationships between TH-ir and circuitry underlying alternative male reproductive behavior are unexplored. Brain CA nuclei and fiber densities are known to be regulated by steroid hormones [Wilczynski et al, 2003; LeBlanc et al, 2007; Kabelik et al, 2011; Matragrano et al, 2013; Barth et al, 2015], and forebrain dopaminergic neurons in midshipman are located in areas replete with androgen and estrogen receptors and aromatase (estrogen synthase) [Forlano et al, 2001, 2005, 2010, 2014]. Importantly, steroid hormone profiles, estrogen receptor expression, as well as aromatase activity and expression are different between male morphs [Brantley et al, 1993; Schlinger et al, 1999; Forlano and Bass, 2005; Fergus and Bass 2013], which may regulate morph differences in CA neuron number and/or their innervation patterns.…”
Section: Introductionmentioning
confidence: 99%